2000
DOI: 10.1111/j.1399-3054.2000.1100406.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐genome derived resistance to Leptosphaeria maculans in near isogenic Brassica napus lines is independent of glucosinolate profile

Abstract: The role of the glucosinolate‐myrosinase system in resistance to Leptosphaeria maculans was studied by monitoring changes in glucosinolate profiles in leaf tissue surrounding the site of inoculation. Susceptible Brassica napus cv. Hanna, resistant B. nigra and near isogenic lines derived from interspecific hybrids between the two species were compared. Expression of myrosinase binding protein and presence of genetic markers were also assayed. No correlation between degree of resistance and amount of sinigrin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…MGBS levels have previously been reported to increase by 30–47% in response to L. maculans infection in Brassica napus after 5–8 days of inoculation (Wretblad and Dixelius, 2000 ). In an in vitro study, Mithen et al ( 1986 ) also reported anti-fungal activity for MGBS along with two other glucosinolates, SIN and GBS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MGBS levels have previously been reported to increase by 30–47% in response to L. maculans infection in Brassica napus after 5–8 days of inoculation (Wretblad and Dixelius, 2000 ). In an in vitro study, Mithen et al ( 1986 ) also reported anti-fungal activity for MGBS along with two other glucosinolates, SIN and GBS.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, no obvious relationship between glucosinolate profiles and L. maculans resistance has been established, possibly due to the fact that these studies focused on total glucosinolate levels rather than individual glucosinolate compounds (Mithen and Magrath, 1992 ; Giamoustaris and Mithen, 1997 ; Sexton et al, 1999 ; Kliebenstein et al, 2002 ). Previous studies concluded that the glucosinolate-myrosinase system is not a major determinant of blackleg resistance (Wretblad and Dixelius, 2000 ; Andreasson et al, 2001 ). This conclusion was supported by an earlier report in resynthesized B. napus F 2 progeny, in which disease resistance and glucosinolate profiles did not co-segregate (Mithen and Magrath, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of GSLs in leaf tissues is a result of concomitant activation of myrosinases (biosynthesis and catabolism), which can upregulate the contents of the GSL components at a specific time period. MGBS levels increased by 30–47% in response to Leptospharia maculans after 5–8 days of infection in B. napus [ 57 ]. In vitro studies have reported the antifungal activity of MGBS, as well as SIN and GBS [ 58 ] and increased accumulation of MGBS conferred moderate resistance in cabbage plants to L. maculans .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that ITCs can inhibit growth of fungal and bacterial pathogens (Brader et al, 2001;Manici et al, 1997;Mithen et al, 1986;Tierens et al, 2001). Earlier in vivo studies of disease resistance of Brassica napus cultivars bred for altered levels of GSs were not conclusive with respect to the role of the individual GSs (Giamoustaris and Mithen, 1997;Li et al, 1999;Wretblad and Dixelius, 2000).…”
Section: Introductionmentioning
confidence: 99%